Efficacy and safety of two “Carmolis” forms for combined local therapy of knee osteoarthritis: results of a multicenter clinical trial - L. N. Denisov; V. N. Sorotskaya; E. A. Leonova; L. V. Меn’shykova; M. L. Sukhareva; S. I. Glukhova; A. M. Lila (Klinicist)
Objective – to evaluate efficacy and safety of “Carmolis” fluid and gel in patients with knee osteoarthritis, as well as the gel efficacy combined with ultraphonophoresis.Materials and methods. The study included 200 patients, who were divided into 2 groups depending on the way of application of “Carmolis” forms. Group 1 included 165 patients with knee osteoarthritis (the main group included 90 patients, the control group – 75 patients), who underwent complex local treatment with 2 “Carmolis” forms. Group 2 included 35 patients (20 people in the main group and 15 in the control one). The main group received phonophoresis with “Carmolis” gel, and the control group received “Carmolis” gel locally on the affected knee joint. Patients’ average age in group 1 was 62,7 ± 8,5 years, the average age in the control group was 61.4 ± 8.7 years, the disease duration was 10.1 ± 4.7 and 9.2 ± 6, 0 years, respectively. In group 2 the average age and disease duration were 60.1 ± 12.8 and 5.7 ± 5.4 years, respectively.At the initial stage 90 patients of the main group 1 were rubbed “Carmolis” fluid locally in the joint followed by massage. After the fluid absorbed completely, “Carmolis” gel was applied, followed by massage. In the comparison group (75 patients), standard therapy was combined only with “Carmolis” fluid applied on the II knee joint.Twenty patients of the main group 2 were treated with phonophoresis combined with “Carmolis” gel. Clinical efficacy was assessed by pain dynamics.Results. Treatment with two “Carmolis” local forms significantly decreased average on moving from 61.8 ± 14.2 to 30.7 ± 14.2 (р <0,001), at rest – from 49 ± 19, 9 to 20.4 ± 8.5 (р <0,001), on palpation – from 38.7 ± 10.4 to 18.4 ± 5.7 (р <0,001). A similar dynamics was also revealed during WOMAC assessment (Western Ontario McMaster Universities OA Index). Before the treatment start the average WOMAC pain level in the main group was 240.5 ± 39.8, after the treatment – 114.8 ± 30.4 (р <0,001). The control group also showed pain decrease, but to a much lesser extent than in the main one. At the end of the treatment course, patients of both groups demonstrated a pronounced decrease of synovitis sings, but there were no differences between the groups. The dose of non-steroidal anti-inflammatory drugs in the main group was reduced in 70 (77.8 %) patients, in the control group – in 50 (66.7 %). The tolerability of both forms was very good and good. No adverse events were registered. Data on the effectiveness and safety of “Carmolis” gel combined with ultraphonophoresis are presented in the article.Conclusion. According to the results, combined therapy using “Carmolis” liquid and gel significantly reduces joint pain and synovitis severity, increases joints» functional ability and improves patients» general condition, which allows reducing the dose of non-steroidal anti-inflammatory drugs. Both “Carmolis” forms had excellent and good tolerability.